Pengaruh Pancasila Terhadap Pertahanan Dan Keamanan Nasional Pada Masa Pilpres 2024 - Assyeh Annassrul; Edy Soesanto (Garuda: Jurnal Pendidikan Kewarganegaraan Dan Filsafat, 2024)
This research needs to be carried out because there may be disturbances in various fields such as economics, politics, defense and state security during the 2024 presidential and vice presidential general elections (PILPRES). Making Pancasila the State ideology to strengthen National Defense and Security in the elections president and vice president are the goals to be achieved. Library research was chosen as the method used in research by collecting legal sources. The data collection method used in this research was a literature survey. The legal data collected was analyzed qualitatively and the author used content analysis to classify legal materials. The results of this research will encourage the public and government to not only focus on holding presidential elections, but also pay attention to the impacts that may arise from this activity, specifically those related to National Defense and Security. By using the values ​​in Pancasila principles 1 to 5 as ideology, it can be concluded that this can strengthen the country's defense and security in the 2024 election.